2015
DOI: 10.3390/su7033071
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay of Air Passengers for Carbon-Offset

Abstract: An important source of anthropogenic greenhouse gas (GHG) emissions is the air transport sector, which accounts for approximately 2% of global GHG emissions. Therefore, reducing GHG emissions from aircrafts has become a major challenge for transportation authorities worldwide. In recent years, much research has focused on tax ideas related to the CO2 emissions produced by air transport, such as the voluntary carbon offset (VCO). This study investigates the willingness of economy class air passengers to pay to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 29 publications
1
29
1
Order By: Relevance
“…The regression analysis revealed that the variables frequentfly, leftpolview, responsible and earmark are all significant predictors of WTP, while from the socio-demographic variables only female is a significant predictor of WTP surcharge and income is a significant predictor of WTP airshort , WTP airlong and WTP aircombined (see Table 2). The latter effect of income on WTP was found in many previous CV studies, also in the context of flying and emissions offsetting (Brouwer et al, 2008;Jou & Chen, 2015;Löschel et al, 2017). The variable female significantly increased the likelihood of being willing to pay (WTP surcharge ), which supports previous evidence for gender differences in environmental behaviour in general (Zelezny, Chua, & Aldrich, 2000) and in WTP for air travel emissions in particular (MacKerron et al, 2009).…”
Section: Personal Factors Influencing Wtpsupporting
confidence: 86%
See 1 more Smart Citation
“…The regression analysis revealed that the variables frequentfly, leftpolview, responsible and earmark are all significant predictors of WTP, while from the socio-demographic variables only female is a significant predictor of WTP surcharge and income is a significant predictor of WTP airshort , WTP airlong and WTP aircombined (see Table 2). The latter effect of income on WTP was found in many previous CV studies, also in the context of flying and emissions offsetting (Brouwer et al, 2008;Jou & Chen, 2015;Löschel et al, 2017). The variable female significantly increased the likelihood of being willing to pay (WTP surcharge ), which supports previous evidence for gender differences in environmental behaviour in general (Zelezny, Chua, & Aldrich, 2000) and in WTP for air travel emissions in particular (MacKerron et al, 2009).…”
Section: Personal Factors Influencing Wtpsupporting
confidence: 86%
“…A complication in the design of air ticket taxation is that there is little information about people's willingness to pay (WTP) for such mandatory taxes. In contrast, various studies have investigated air travellers' WTP for voluntary offsets (Brouwer, Brander, & Van Beukering, 2008;Choi & Ritchie, 2014;Jou & Chen, 2015;Lu & Shon, 2012;MacKerron, Egerton, Gaskell, Parpia, & Mourato, 2009). However, this information is not particularly useful for the design of air ticket taxes as there are strong indications that WTP is systematically lower for voluntary offsets than for coercive instruments (Segerstedt & Grote, 2016;Wiser, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We represent the weight of each factor by using the variance contribution rate of each factor divided by the total variance contribution rate (69.77%) of all six factors. The scores of the six factors were weighted and summed using Equation (6) to calculate the comprehensive value for the pro-environmental motivation (F).…”
Section: Factor Analysis Of Pro-environmental Motivationmentioning
confidence: 99%
“…The transport energy consumption of urban areas is larger than that of rural areas, which is about 10%-15% of the total energy consumption [5]. Due to the rapid growth of the ownership of private cars in cities, traffic congestion not only seriously affects residents' normal lives, but also exacerbates urban air pollution caused by the rapid increase in greenhouse gas emissions [6]. China's CO 2 emissions in the urban transportation…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable transportation policies are closely related to the potential contribution of this sector in order to decrease in CO 2 emissions [1][2][3]. Air quality and carbon dioxide emissions, especially in urban transportation and air transportation, is one of the major points of interest of researchers [4]. The concern of car manufacturers of air quality inside and outside the vehicle should combine and satisfy both the problematic aspects related to comfort and those related to traffic safety, without neglecting any aspects of reducing energy consumption.…”
Section: Introductionmentioning
confidence: 99%